Використання ризик-інформованих підходів в інспекційній діяльності - Gromov, G.; Dybach, O.; Sevbo, O.; Gashev, M.; Boychuk, V. (State Scientific and Technical Center for Nuclear and Radiation Safety, 2010)
Application of risk-informed approaches allows focusing inspections on design and operation aspects that have a major impact on NPP safety, improvement and justification of inspection planning, and quantitative assessment of inspection findings. The article contains the methodology for application of risk-informed approaches in inspections, includes information on prepared guidelines and technical documents and proposals on future work.